Improving Class 5 Student Learning Outcomes Theme 4 Sub-theme 2 Using the Discovery Learning Model - Widayanti, Nanik (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve the learning outcomes of grade 5 students using. The research conducted was Classroom Action Research (CAR) which was conducted in three cycles. Each cycle consists of four stages, namely planning, implementing, observing and reflecting. Each meeting is carried out an evaluation in the form of a written test to determine the development of students. In the first cycle, the students who completed the evaluation were 60%. In cycle II students who completed after evaluating were 80%. In the third cycle, students who completed after evaluating were 87.5%. These results indicate that the Discovery Learning learning model can improve student learning outcomes, especially Theme 4 Subtema 2 Class V at SDN 2 Tanjungharjo.